Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1136/sti.2007.027375
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic treatment of symptomatic Mycoplasma genitalium infection in Scandinavia: a controlled clinical trial

Abstract: Azithromycin was more effective than doxycycline in treating patients infected with M genitalium. The extended course of azithromycin was highly effective but was given after the initial treatment with doxycycline. Randomised clinical trials are needed to compare the different dosages of azithromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 30 publications
5
131
0
3
Order By: Relevance
“…The susceptibility of M. genitalium to various antibiotics is outlined in Table 3 and presented in more detail elsewhere (226). Although tetracyclines were used to treat NGU before M. genitalium was discovered, they are not the antibiotics of choice for M. genitalium-associated disease (12,145). This was also true for women for whom cefoxitin and doxycycline failed to eradicate endometrial M. genitalium (63).…”
Section: Antimicrobial Susceptibility Treatment and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility of M. genitalium to various antibiotics is outlined in Table 3 and presented in more detail elsewhere (226). Although tetracyclines were used to treat NGU before M. genitalium was discovered, they are not the antibiotics of choice for M. genitalium-associated disease (12,145). This was also true for women for whom cefoxitin and doxycycline failed to eradicate endometrial M. genitalium (63).…”
Section: Antimicrobial Susceptibility Treatment and Preventionmentioning
confidence: 99%
“…Since then, M. genitalium has been found in up to 40% of men presenting with chronic disease after treatment with doxycycline (209,229). Indeed, in several clinical studies (36, 82, 83, 134, 205, 229), a strong correlation was found between M. genitalium infection and persistent or recurrent NGU, probably due to tetracyclines and, more recently, azithromycin (17, 18) eradicating M. genitalium from only a subset of the patients (12,46). Other aspects of treatment are discussed below.…”
Section: Chronic Ngumentioning
confidence: 99%
“…An extended regime (1.5 g over 5 days) is often prescribed if singledose AZM is unsuccessful, but there is contention regarding the effectiveness of this extended treatment (19,20). Alarmingly, studies investigating the effectiveness of either 1 g or 1.5 g AZM treatment have reported microbiological treatment failure in 16% to 33% of patients (19,(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…18 In one study, M. genitalium eradication rates in women treated with azithromycin were 88% compared with 37% with doxycycline. 19 Azithromycin is available locally, and the treatment cost for 1 g in Haiti ranges from 40 to 200 Haitian Gourdes (US $0.93-$4.65). In addition to providing coverage for both C. trachomatis and M. genitalium, a single dose of azithromycin also has the advantage of use in directly observed therapy (DOT) protocols for immediate onsite treatment.…”
Section: Discussionmentioning
confidence: 99%